Management v športu: Izbrana poglavja (University of Maribor Press, 2023)
Management in Sports: Selected Chapters. The scientific monograph Management in Sport - Selected Chapters covers areas that primarily relate to the field of sport in relation to various elements of management and governance and broader aspects of society. The content of the monograph is primarily up-to-date and follows the needs of linking scientific content with applied effects. The chapters, which are part of the scientific monograph and which include an appropriate degree of interdisciplinarity, should be a springboard far the study and upgrading of the knowledge of students, the academic public and society at large.